Factors Affecting the Implementation Process of Pertussis [Tdap] Immunization in Pregnant Women in an Italian Region: A Qualitative Study - Mazzilli, Sara; Tavoschi, Lara; Lopalco, Pier Luigi (Frontiers in Public Health, 2020)
Whooping cough (pertussis) represents one of the most prevalent vaccine-preventable diseases in Western countries, capable of causing disease in infants, with a high risk of severe complications. To protect new-borns from pertussis, many countries have introduced the acellular pertussis adult vaccine in combination with tetanus and diphtheria toxoids for women in the third trimester of pregnancy. Thanks to the approval of the new National Immunization Prevention Plan 2017–2019: Italy is among those countries. The Italian health-care system is a regionally based National Health Service, therefore, regions organize and implement new vaccination strategy on their own. This study focuses on Tuscany's experience in implementing the maternal pertussis vaccination. The present study had a qualitative design: we obtained information about the implementation process through interviews with relevant stakeholders involved in the planning or implementation of vaccination programme at different levels. We noticed heterogeneous implementation's status between Tuscan Health Care Departments. The most frequently reported barriers influencing the success of the implementation process of this prevention strategy included: lack of accountability, lack of enabling instruments, financial constraints, logistics barriers, training deficiencies, attitudes of health care workers, and lack of communication experts. The implementation of new vaccination programs is complex and challenging. Often the importance of education and information activities targeting health professionals are underestimated and underfunded. These elements would need to be carefully considered and adequate provisions should be made to address them when designing and implementing effective vaccine interventions.